2003
DOI: 10.1002/mus.10418
|View full text |Cite
|
Sign up to set email alerts
|

Two novel mutations in the muscle glycogen phosphorylase gene in McArdle's disease

Abstract: We report on a Spanish family with myophosphorylase (EC 2.4.1.1) deficiency (McArdle's disease). The proband and his symptomatic sister were compound heterozygous for two novel mutations: a T-to-G transversion in exon 14 (c1722 T>G) that changes a tyrosine to a stop codon (Y573X), and a G-to-A transition in exon 15 (c1827 G>A) that disrupts the consensus signal at the donor splicing site. These findings further expand knowledge of the genetic bases of muscle glycogen phosphorylase deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Also, two frequent ethnic mutations have [26] *Recently identified in cDNA, it is likely an inotronic mutation that affects splicing at the cDNA level or it is a genomic deletion. Gamez et al [63] *Recently identified in cDNA, it is likely an inotronic mutation that affects splicing at the cDNA level or it is a genomic deletion. Bruno et al [18••] *Recently identified in cDNA, it is likely an inotronic mutation that affects splicing at the cDNA level or it is a genomic deletion.…”
Section: Pygm Mutationsmentioning
confidence: 98%
“…Also, two frequent ethnic mutations have [26] *Recently identified in cDNA, it is likely an inotronic mutation that affects splicing at the cDNA level or it is a genomic deletion. Gamez et al [63] *Recently identified in cDNA, it is likely an inotronic mutation that affects splicing at the cDNA level or it is a genomic deletion. Bruno et al [18••] *Recently identified in cDNA, it is likely an inotronic mutation that affects splicing at the cDNA level or it is a genomic deletion.…”
Section: Pygm Mutationsmentioning
confidence: 98%